Vision loss in glioblastoma: Disease mimicking presumed therapeutic toxicity. Issue 4 (2nd February 2018) - Nguyen, HuyTram N; Vo, Kevin B H; Howard, Steven; Salamat, M Shahriar; Rowely, Howard; Robins, H Ian
Abstract: Glioblastoma is the most common and lethal form of primary brain cancer. In the recurrent setting, bevacizumab is a common choice for salvage therapy. Loss of vision in patients initially treated with radiation at the time of diagnosis and later treated with bevacizumab at time of recurrence has been reported, and presumed to be a treatment-related optic neuropathy. Strikingly, only 1 case report described a postmortem biopsy to rule out tumor involvement of the optic tracts. We report the first case of recurrent glioblastoma infiltrating the prechiasmatic and chiasmatic optic nerve, which at the time of vision loss was presumed to be secondary to bevacizumab. It is noteworthy that the MRI findings in the previously reported bevacizumab/radiation-induced optic neuropathy cases (without pathology follow-up) are comparable to our patient.